Inevitable to bring back the ISA - Daily Express, (KK) (Daily Express (KK), 2014)
KUALA LUMPUR: The Internal Security Act (ISA) should be brought back, if necessary under a new name, as there appears to be widespread public support for a strong preventive law.Universiti Utara Malaysia's College of Law and International Relations dean Prof Dr. Ahmad Marthada Mohamed said such a preventive law was indeed necessary and timely.